Biocompatible Packaging of an Epicardial Accelerometer for Real-time Assessment of Cardiac Motion. (2016) - Brancato, L.; Weydts, T.; Oosterlinck, W.; Herijgers, P.; Puers, R.
Abstract: An implantable accelerometer has been developed to monitor the cardiac function and the heart wall motion. The device, to be stitched on the pericardium, can also provide an insight on amplitude and frequency components of the acceleration on different locations on the heart. A commercially available three-axis accelerometer was mounted on a miniature PCB and coated with Parylene-C. The PCB was glued on a laser-cut Teflon structure and then embedded in PDMS. The structural flexibility of the assembly allows the device to adapt to the natural curvature of the muscle and to stretch, therefore not limiting the natural movement of the underlying tissue. The device was tested in-vitro for current leakage and water diffusion. The in-vivo performance was evaluated by recording acceleration signals from the heart of a sheep.